Analisis Keterampilan Shooting Pada Permainan Sepakbola Di Smp Negeri 39 Seluma - Saputra, Riko Gion; Febrianti, Mariska; Putra, Dwingki Marta (CV. Generasi Insan Rafflesia, 2024)
This study aims to determine the shooting skills in football games at SMP Negeri 39 Seluma. This type of research is qualitative descriptive research. The research sample consisted of 25 people. The instrument used in this study was the Football Shooting Test. Where the results of the analysis of shooting skills in football games at SMP Negeri 39 Seluma in this study showed the classification of